Does Heart Rate Variability Better Differentiate Individuals With and Without an Anxiety Disorder at Rest or During Stress? - Lavery, Callan Oscar (Curtin University, 2022)
This thesis includes two studies examining heart rate variability (HRV) in clinically anxious and control participants. The first is a meta-analysis comparing HRV in clinically anxious and non-anxious samples, at rest and during a disorder relevant stress task. The second is an experimental study examining whether HRV better differentiates between individuals with vs. without social anxiety disorder at rest or during social stress. These findings may inform novel treatment and diagnosis approaches for anxiety disorders.